2017
DOI: 10.15761/jsin.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Chronic purple grape juice consumption induces age-dependent changes on cognitive function in elderly women

Abstract: Objective: To verify the chronic consumption of grape juice effects on weight, body mass index (BMI), cognitive function and the peripheral levels of global histone H4 acetylation, BDNF and inflammatory markers in elderly women according to age. Methods: This is a quasi-experimental study. The blood samples were collected before and after 30 days of grape juice supplementation (400 ml/daily) in women aged > 70 and < 70 years old. Weight, BMI and cognitive function, were measured before and after supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…we observed that the consumption of grape juice reduced the protein oxidation damage (Carbonyl levels). Corroborating our findings, healthy older adults who received 400 mL/day of purple grape for thirty days presented significant reduction in the levels of oxidative damage to proteins [33], but with a significant increase at superoxide dismutase activity, different from our study. This divergence could be partially explained because in the research conducted by Da Costa (2015) the participants were submitted only to the consumption of grape juice without the practice of physical exercise [33].…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…we observed that the consumption of grape juice reduced the protein oxidation damage (Carbonyl levels). Corroborating our findings, healthy older adults who received 400 mL/day of purple grape for thirty days presented significant reduction in the levels of oxidative damage to proteins [33], but with a significant increase at superoxide dismutase activity, different from our study. This divergence could be partially explained because in the research conducted by Da Costa (2015) the participants were submitted only to the consumption of grape juice without the practice of physical exercise [33].…”
Section: Discussioncontrasting
confidence: 95%
“…During the intervention period, ACQ-EXE þ GJ also drunk the juice, consuming 400 ml/daily. This grape juice amount was in accordance to the literature [31,33]. It was recommended for ACQ-EXE group to avoid grape derivates, grape juice, and wine.…”
Section: Methodsmentioning
confidence: 55%
See 2 more Smart Citations
“…Several studies have shown that polyphenols, especially anthocyanins and copigments, have antioxidant, anti-inflammatory, anti-bacterial, and anti-viral properties and are discussed in the context of influencing glucose and lipid metabolism in vitro as well as in vivo [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%